2007
DOI: 10.1002/art.22292
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of vitamin D and worsening of knee osteoarthritis: Results of two longitudinal studies

Abstract: Objective. To confirm reports that 25-hydroxyvitamin D (25[OH]D) deficiency is associated with an increased risk of joint space narrowing or cartilage loss in osteoarthritis (OA). Methods. We measured 25(OH)D levels in sub-Osteoarthritis (OA) is characterized by loss of cartilage and concurrent changes in subchondral bone, and there is evidence that subchondral bone has a major influence on the development of OA and its worsening

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
123
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(132 citation statements)
references
References 21 publications
2
123
0
4
Order By: Relevance
“…In participants of the "Framingham Study", low serum 25-OHD predicted the development of cartilage loss and knee OA progression [14]. However, the association of vitamin D deficiency and OA was not confirmed by another longitudinal study by Felson et al [16].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In participants of the "Framingham Study", low serum 25-OHD predicted the development of cartilage loss and knee OA progression [14]. However, the association of vitamin D deficiency and OA was not confirmed by another longitudinal study by Felson et al [16].…”
Section: Discussionmentioning
confidence: 95%
“…Up to now most studies addressed the association between OA and serum 25-OHD in longitudinal studies [5,6,[14][15][16][17]. No study has yet compared serum 25-OHD levels between OA patients and controls.…”
Section: Discussionmentioning
confidence: 99%
“…However more recent results from two longitudinal cohort studies, the Framingham Offspring cohort (715 subjects) and the Boston Osteoarthritis of the Knee Study (BOKS) (277 subjects) [125] found no association of baseline 25(OH)D concentration with radiographic worsening of joint space narrowing nor any relationship with cartilage loss.…”
Section: Vitamin D In Ramentioning
confidence: 95%
“…Although vitamin D was also shown to be an important hormonal contributor to cartilage and chondrocyte homeostasis and vitamin D receptors are present in chondrocytes [152], its role in OA is far less understood and still controversial. Indeed, while some clinical studies reported that vitamin D deficiency was associated with an increased risk of progression of knee OA and incidence of hip OA [153,154], others demonstrated no association between serum vitamin D levels and joint space loss or worsening cartilage score in knee OA [155,156]. Most of these studies used radiographic assessment of OA and one also employed MRI.…”
Section: Drugs/agents That Target Bone Remodellingmentioning
confidence: 99%
“…Most of these studies used radiographic assessment of OA and one also employed MRI. However, in the study using MRI [155], the authors did not assess the whole knee or cartilage volume. Interestingly, in a recent study [157] in which the assessment of knee OA structural changes was performed both radiographically and by quantitative MRI, a change in serum vitamin D level was positively associated with change in cartilage volume.…”
Section: Drugs/agents That Target Bone Remodellingmentioning
confidence: 99%